Penalaran Aljabar dalam Menyelesaikan Operasi Bilangan Berpangkat Berdasarkan perspektif Woston (2007) Pada Materi Relasi Fungsi Kelas VIII - nada, FITHROTUN (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the forms of algebraic reasoning demonstrated by eighth-grade junior high school students in solving exponential function problems, based on Watson’s (2007) perspective. The research was conducted using a descriptive approach with instruments consisting of written questions and interview guidelines. The results show that students exhibit indicators of algebraic reasoning such as symbolic manipulation, understanding of function structure, problem-solving strategies, mathematical communication, and basic reflection. These findings highlight the importance of strengthening instructional practices that emphasize conceptual thinking processes and mathematical communication in the topic of relations and functions.